Kebijakan Pertahanan Strategis: Mendefinisikan Ulang Pengadaan Alat Peralatan Pertahanan dan Keamanan sebagai Investasi, Bukan Pemborosan - Sarjito, Aris (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2024)
This research explores the strategic defense policy of redefining equipment procurement as an investment rather than a waste, focusing on its contributions to economic growth and technological innovation. The study aims to demonstrate how defense equipment procurement can stimulate economic development and drive technological advancements, while also optimizing procurement processes. Utilizing qualitative research methods and secondary data, including policy reports, industry analyses, and academic literature, the study provides a comprehensive examination of the economic and technological impacts of defense procurement. Key findings reveal that defense procurement significantly contributes to economic growth by creating jobs, stimulating GDP, and fostering technological innovation through advancements in artificial intelligence, cybersecurity, and unmanned systems. The research also highlights the strategic value of investing in advanced military technologies for national security and identifies best practices and policy measures to enhance procurement efficiency. By analyzing successful case studies and policy frameworks, the study offers actionable recommendations for optimizing defense procurement processes. The conclusion underscores the importance of viewing defense procurement as a strategic investment that delivers substantial economic and technological benefits. Keyword: defense equipment procurement; economic growth; strategic defense policy; technological innovation.